The impact of regulatory change on hedge fund performance - Fan Yang (Charles University in Prague, Institute of Economic Studies (IES), 2023)
The paper investigates the effect of recent EU regulations on hedge fund performance. The expansion of hedge funds attracts the attention from authorities who are responsible for monitoring the market risks but the influence of the oversight has been argued for a long time. Prior studies usually focus on the US regulations and they provide controversial findings about the relationship of hedge fund performance and regulations. However, to our knowledge, no studies discuss the impact of the EU regulations-the Alternative Investment Fund Manager Directive (AIFMD). The analysis of the AIFMD and the comparison of the rules from the US and the EU show that the EU Directive has more extensive requirements, compliance cost, and wider scope of disclosure to the public. Considering the additional compliance cost and higher possibility to reveal managers' strategies, we expect the hedge fund performance is negatively influenced by the EU regulation. Based upon the common difference-in-difference method (DID), we utilize the characteristic that the scope of the AIFMD exempts some EU hedge funds and add the third factor to formulate the triple difference method to test the triple interaction relationship. This method allows us to mitigate the different influence from potential various sensitivities or development speed from control group and treatment group. Our results show that hedge funds domiciled or marketed in the EU had a drop of 0.2% in the alpha. The result has been further enhanced by comparing the matched control group and treatment group by using the propensity matching score, which ensures our research compares the changes of individual authorized hedge funds based on the specified authorization date.
Keywords: G23; G28; 330; hedge fund; regulation; stock returns